2022
DOI: 10.3390/ijms23179943
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Pathways and Mechanisms of Colored Secondary Metabolites in Cancer Therapy

Abstract: Despite the great advancements made in cancer treatment, there are still many unsatisfied aspects, such as the wide palette of side effects and the drug resistance. There is an obvious increasing scientific attention towards nature and what it can offer the human race. Natural products can be used to treat many diseases, of which some plant products are currently used to treat cancer. Plants produce secondary metabolites for their signaling mechanisms and natural defense. A variety of plant-derived products ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 180 publications
1
5
0
Order By: Relevance
“…The survival test results suggest that a higher concentration of BPF may induce less survivability for both breast cancer cell lines. This is a desirable effect, since BPF is a natural source of compounds that could be added to the diet in order to promote possible anticancer activity that may aid cancer treatment, increasing treatment efficiency [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival test results suggest that a higher concentration of BPF may induce less survivability for both breast cancer cell lines. This is a desirable effect, since BPF is a natural source of compounds that could be added to the diet in order to promote possible anticancer activity that may aid cancer treatment, increasing treatment efficiency [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extracts have obtained been from different parts of the beetroot plant, such as the flesh [ 8 ], leaves [ 2 ], roots [ 9 ] and peel [ 10 ], with betalains and polyphenols receiving great attention. Betalains have previously been reported not only as antioxidants [ 11 ] but also as molecular agents that act via different pathways, such as via the inhibition of the mTOR pathway, the positive modulation of the caspases pathway [ 12 ], and the activation of the p53 pathway [ 6 ], leading to the modulation of the cell cycle and apoptosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate , a secondary metabolite of Artemisia annua , has demonstrated efficacy against a variety of cancer types, with leukemia and colon cancer showing the greatest sensitivity (Khan et al., 2019). Quercetin , a polyphenolic flavonoid of plant origin, exhibits a multi‐targeted anticancer effect by inducing apoptosis in human epidermoid carcinoma cells KB and KBv200 through the reduction of mitochondrial membrane potential (Sevastre et al., 2022). The study has identified several secondary metabolites in Chinese torreya nuts, including (S)‐4‐hydroxymandelate, 3‐hydroxyanthranilic acid, and pipecolic acid, which have the potential to modulate sex hormones in mice (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…39 Lichens' secondary metabolites could be significant in cancer treatment since they are less toxic than regular chemotherapeutic drugs like tamoxifen and paclitaxel. 40 Many studies have reported that numerous lichens possess antitumor activity against different cancer cells, such as colon carcinoma (HT-29), hepatocellular carcinoma (Hep-G2), and breast cancer cell line (MCF-7). [41][42][43] Previous studies have shown that UA has numerous biological and pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoprevention is a promising approach for controlling cancer numbers and creating new chemotherapeutic drugs 39 . Lichens' secondary metabolites could be significant in cancer treatment since they are less toxic than regular chemotherapeutic drugs like tamoxifen and paclitaxel 40 . Many studies have reported that numerous lichens possess antitumor activity against different cancer cells, such as colon carcinoma (HT‐29), hepatocellular carcinoma (Hep‐G2), and breast cancer cell line (MCF‐7) 41–43 .…”
Section: Discussionmentioning
confidence: 99%